Evaluación de la estrategia de implementación de negocios verdes en Colombia en el periodo 2005 2015 (2018)
The implementation of the Green Business in Colombia is an opportunity of economic growth I dress from the care and awareness with the use of natural resources and the environment and the diversification of exporting offer promoting the competitiveness, nevertheless the strategy of the Green Business in Colombia is in full implementation, but in spite of the existence of the above mentioned programs and plans, the country is in a zone of I leave behind with regard to the economies of the world, departing from this it turns out to be pertinent to do an evaluation on the progress that the Green Business have had in Colombia during the period 2005 - 2015 and which are the reasons of his behavior. Given the importance that would have the creation of niches of market of this type is born the need to investigate which has been his behavior and to evaluate the result of his implementation in Colombia during the period understood between 2005 and 2015, one refers to the importance of the Green Business for the useful thing that results for the Sustainable Development in the countries, according to Jose Carlomarde the economic development can be promoted across the minimization of the consumption of natural resources and the deterioration of the nature, of this form one would be speaking about an integral development summarized in Sustainable Development, which there join economic, human, social and ecological factors, about this form.